The Desultory Politics of Mobility and the Humanitarian-Military Border in the Mediterranean. Mare Nostrum Beyond the Sea - Tazzioli, Martina (2015)
This article investigates the reshaping of the military-humanitarian border in the Mediterranean, focusing on the Italian militaryhumanitarian mission Mare Nostrum, that started for rescuing migrants at sea after the deaths of hundreds of migrants in October 2013 near the coasts of the island of Lampedusa. The main argument is that in order to understand the working of the military-humanitarian border at sea and its impacts, we must go beyond the space of the sea, and analysing it in the light of the broader functioning of migration governmentality. The notion of desultory politics of mobility is deployed here for describing the specific temporality of the humanitarian border working and its politics of visibility. In particular, an analytical gaze on the military-humanitarian operations at sea to rescue-and-control of migrants’ movements shows that what is at stake is the production of some practices of mobility as exceptional. Then, this article takes on Mare Nostrum operation for exploring the ways in which the military and the humanitarian are rearticulated and how they currently work together. Este artigo investiga a remodelação da fronteira militar-humanitária no Mediterrâneo, com enfoque na missão militar-humanitária da Itália, Mare Nostrum, que começou com o intuito de resgatar migrantes no mar após as mortes de centenas de migrantes, em outubro de 2013, perto da costa da ilha de Lampedusa. O argumento principal é que, para entender a ajuda militar-humanitária no mar e os seus impactos, é preciso ir além do espaço marítimo e analisá-la à luz do funcionamento mais abrangente da governamentalidade da mobilidade. A noção de políticas intermitentes de mobilidade é usada para descrever a temporalidade específica da ajuda humanitária na fronteira e a sua política de visibilidade. Mais especificamente, um olhar analítico sobre as operações militareshumanitárias no mar para resgate-e-controle do movimento dos migrantes mostra que o que está em jogo são algumas práticas de mobilidade como exceção. Em seguida, este artigo usa a operação Mare Nostrum para explorar como o militar e o humanitário são rearticulados e como atualmente funcionam juntos.